1991
DOI: 10.1002/bjs.1800781011
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized trial of Nissen fundoplication and Angelchik prosthesis in the surgical treatment of medically refractory gastro-oesophageal reflux disease

Abstract: Fifty patients with gastro-oesophageal reflux disease refractory to multiple courses of medical therapy were entered into a prospective randomized trial comparing Nissen fundoplication with the Angelchick prosthesis as a primary surgical procedure. The two groups were matched for age, sex, duration of symptoms before surgery, type of medical therapy, pattern of symptom presentation, endoscopic grade of oesophageal inflammation, manometric lower oesophageal pressure and 24-h pH profile. Twenty-five patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…Reports of the laparoscopic adjustable gastric banding operations seem to be con¯icting. In theory, the adjustable band prevents re¯ux in a manner similar to the, 3 Angelchick prosthesis, which is placed around the lower esophagus rather than the upper stomach [16]. Dixon and O'Brien reported 90% resolution or improvement in GERD in 48 patients who underwent laparoscopic gastric banding with a preoperative diagnosis of GERD [8].…”
Section: Discussionmentioning
confidence: 98%
“…Reports of the laparoscopic adjustable gastric banding operations seem to be con¯icting. In theory, the adjustable band prevents re¯ux in a manner similar to the, 3 Angelchick prosthesis, which is placed around the lower esophagus rather than the upper stomach [16]. Dixon and O'Brien reported 90% resolution or improvement in GERD in 48 patients who underwent laparoscopic gastric banding with a preoperative diagnosis of GERD [8].…”
Section: Discussionmentioning
confidence: 98%
“…Other investigators have reported a reoperation rate of 5-15%, with dysphagia also representing the most common reason for Angelchik removal [5, 7-9, 15, 16]. Five prospective randomized trials comparing the Angelchik ring with Nissen fundoplication [6][7][8][9]16] indicated that the Angelchik prosthesis relieves GERD symptoms as well as the Nissen procedure in the early postoperative period. However, several investigators believe that, unlike Nissen fundoplication, the incidence of dysphagia increases over time in patients with the Angelchik ring, most likely due to the formation of dense fibrous pseudocapsules around the silicone prostheses [4,13,17].…”
Section: Discussionmentioning
confidence: 96%
“…Although several studies have suggested that the Angelchik ring provides early postoperative control of GERD symptoms as well as the Nissen fundoplication (NF), reoperation for removal of Angelchik rings due to dysphagia has been necessary in 5-15% of patients [5][6][7][8][9]16]. Furthermore, the Angelchik prosthetic ring has been associated with other complications, including migration into the mediastinum and distant sites within the peritoneal cavity, as well as erosion into the gastrointestinal tract.…”
mentioning
confidence: 99%
“…In mehreren randomisierten Arbeiten fiel u È berdies das funktionelle Langzeitergebnis der Angelchick-Prothese gegenu È ber der Nissen-Fundoplicatio signifikant schlechter aus [27,34,52]. 6) [4].…”
Section: Alternativen Zur Fundoplicatiounclassified